Recognition of a Caucasoid HLA‐B locus allele, B*44:55, in a Taiwanese/Chinese bone marrow stem cell donor. (3rd August 2012) - Yang, K. L.; Lee, S. K.; Kao, R. H.; Lin, C. L.; Lin, P. Y.
Summary We detected a Caucasoid HLA‐B allele, HLA‐B*44:55, in a potential Taiwanese/Chinese bone marrow hematopoietic stem cell donor during our routine HLA SBT (sequence‐based typing) practice. The sequence of B*44:55 varies with B*44:02:01:01 with one nucleotide in exon 2 at position 97 (T‐>C), while it differs from B*44:03:01 with one nucleotide in exon 2 at position 97 (T‐>C) and three nucleotides in exon 3 at residues 538–540 (CTG‐>GAC). The nucleotide replacements caused one amino acid variation with B*44:02:01:01 at residue 9 (Y‐>H) and two amino acid variations with B*44:03:01 at residue 9 (Y‐>H) and residue 156 (L‐>D). The formation of B*44:55 is probably the result of a nucleotide substitution involving B*44:02:01:01 at position 97 (T‐>C). The Taiwanese/Chinese donor with B*44:55 claims having no kinship with Caucasian. Our speculations on the origin of the Taiwanese/Chinese B*44:55 will be presented.